Asal Mula Manusia Menurut Teori Darwin dan Kajian Islam - Zumi Nur Faiza; Syarifuddin Syarifuddin; Enilda Dwi Lestari; Riski Suwandi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Many people think humans were created from monkey. Therefore, reseachers want to make people know that there is another opinion that says humans were not created from apes. The purpose of this research is to increase the reader's insight. Reseachers used the library reseach method, namely by reading lost of books. The result is according to Darwin's theory humans do not originate from apes but belong to the same kingdom Animalia as apes, so it can be interpeted that humans are almost similiar to apes but do not originate from apes. According to islamic teachings, humans were created from soil.